1999
DOI: 10.1029/1999wr900111
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of area‐average sensible heat flux using a large‐aperture scintillometer during the Semi‐Arid Land‐Surface‐Atmosphere (SALSA) Experiment

Abstract: Abstract. The use of a large-aperture scintillometer to estimate sensible heat flux has been successfully tested by several investigators. Most of these investigations, however, have been confined to homogeneous or to sparse with single vegetation-type surfaces. The use of the scintillometer over surfaces made up of contrasting vegetation types is problematic because it requires estimates of effective roughness length and effective displacement height in order to derive area-average sensible heat from measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The LAS appears to be reliable under dry unstable conditions over homogeneous fields, as shown by De Bruin et al (1995), McAneney et al (1995), and Meijninger and De Bruin (2000). Chehbouni et al (1999Chehbouni et al ( , 2000 and Meijninger et al (2002b) have shown that the method also works well over heterogeneous surfaces, while Hoedjes et al (2002) found very promising results over a homogeneous irrigated wheat field affected by regional advection. Hartogensis et al (2003) have demonstrated the possibility of determining an effective height for scintillometers, enabling its operational use over a slant path or over nonflat terrain.…”
Section: Introductionmentioning
confidence: 90%
“…The LAS appears to be reliable under dry unstable conditions over homogeneous fields, as shown by De Bruin et al (1995), McAneney et al (1995), and Meijninger and De Bruin (2000). Chehbouni et al (1999Chehbouni et al ( , 2000 and Meijninger et al (2002b) have shown that the method also works well over heterogeneous surfaces, while Hoedjes et al (2002) found very promising results over a homogeneous irrigated wheat field affected by regional advection. Hartogensis et al (2003) have demonstrated the possibility of determining an effective height for scintillometers, enabling its operational use over a slant path or over nonflat terrain.…”
Section: Introductionmentioning
confidence: 90%
“…Over heterogeneous surfaces (i.e., transect of two patches), effective displacement height and effective roughness 14 length are obtained following Shuttleworth et al (1997) and Chehbouni et al (1999) respectively, which, wi is the fraction of the surface covered by the patch i, and zb is the blending height which is expressed as a function of the friction velocity, wind speed, and horizontal length scale (Wieringa, 1986).…”
Section: Estimation Of Effective Scintillometer Heightmentioning
confidence: 99%
“…In semi-arid ecosystems, water is typically the limiting resource restricting plant productivity and, through plant transpiration and soil evaporation, controls the partitioning of surface energy fluxes into sensible and latent heat fluxes (Chehbouni et al, 2000;Huxman et al, 2004;Rodriguez-Iturbe and Porporato, 2004;Small and Kurc, 2003;Unland et al, 1999). From a land-atmosphere coupling perspective, soil moisture availability can provide a critical constraint on short and long-term memory of previous climatic forcing (e.g.…”
Section: Introductionmentioning
confidence: 99%